The most important reasons for the weakness of the student’s attendee to daily lectures from their point of view: a procedural study of the Faculty of Physical Education and Sports Science / University of Diyala - Ibrahim, HayderSubhi; Hameed Wadi, Hiba (International Journal of Psychosocial Rehabilitation, 2020)
The current study aimed to identify a group of factors that cause the late students’ behavior of the College of Physical Education and Sports Sciences, University of Diyala, from their point of view of lectures. The study sample consisted of 80 male and female students who were selected by a simple random method. A questionnaire consisting of 17 items was prepared that reflects the reasons affecting the behavior of students being late for daily lectures. The data were processed through frequencies, percentages, arithmetic means, standard deviations, and one-way analysis of variance to answer the study questions. The results of the study came to the students who responded to the study questionnaire that there are a number of factors that cause the behavior of students to be late for lectures from their point of view, such as: traffic congestion, sleeping late, being away from the university, long lecture times, daily routine of lectures, inability to choose lecture times in proportion to students’ times.